Relationship Between Anti-Mullerian Hormone (AMH) and Other Influencing Factors with in Vitro Fertilization (IVF) Outcome of Iraqi Infertile Women - Mohammed, Lubna S.; Haddad, Namir I.A. (Iraqi Journal of Science, 2024)
The clinical application of Anti-Mullerian Hormone (AMH) measurement has been proposed in the prediction of qualitative and quantitative aspects of assisted reproductive technologies (ART). The aim of this study is to investigate the role of AMH level and other influencing factors in the outcomes of in vitro fertilization (IVF) treatment. The study focused on AMH and its association with infertile women undergoing IVF. The population included in this study was 131 infertile women who sought therapy for infertility at Kamal Al-Samarra'ay Specialized Hospital. They were divided into three groups according to the level of AMH hormone; group A (0.5-1.5 ng/mL, n=52), group B (1.6-4 ng/mL, n=70), and group C (> 4 ng/mL, n=9). Data collection was performed by means of a specially designed questionnaire, independent of demographic data. It included questions related to infertility. Statistical analysis was performed with SPSS 26. Clinical parameters of infertile women, infertility hormones and their relationship with AMH, as well as FMS-like Tyrosine kinase 1 levels, were all investigated. The study findings revealed a significant difference in the concentration of AMH between infertile women (p<0.01). Our analysis further demonstrated that the level of AMH reduces with advancing age in infertile women. Additionally, a positive correlation was observed between the number of oocytes obtained and AMH levels in infertile women. Furthermore, the study found that AMH levels had an effect on clinical pregnancy outcomes. Specifically, the highest success rates for IVF were observed in women with normal AMH levels falling within the ranges of group B (6-4 ng/mL(. Additionally, the study demonstrated significant differences in AMH and TSH levels among infertile groups (p<0.05). Our study concluded that there is a significant correlation between clinical parameters and IVF outcomes, which can provide information for future clinical interventions aimed at improving success rates. Our analysis highlighted the role of FMS-like Tyrosine kinase 1 in infertility, where higher FMS-like Tyrosine kinase 1 levels were associated with higher success rates in IVF. The results indicate that the FMS-like Tyrosine kinase 1 level is a valuable marker for confirming the success or failure of IVF and can help determine the appropriate treatment plan.